The Effectiveness of Using Learner Worksheets (LKPD) Based on Problem Based Learning (PBL) and Numbered Head Together (NHT) Cooperative Learning Models on Islamic Cultural History Learning Outcomes at MTs Arifah Gowa Regency - Suryadi, Ahmad; Nurlathifah Thulfitrah B. (Proceeding International Conference on Religion, Science and Education, 2024)
The objectives of this study are: (1) Describing the learning outcomes of Islamic Cultural History taught using the Learner Worksheet (LKPD) based on the Problem Based Learning (PBL) learning model at MTs Arifah Gowa. (2) Describing the learning outcomes of Islamic Cultural History taught using the Learner Worksheet (LKPD) based on the Numbered Head Together (NHT) type cooperative learning model at MTs Arifah Gowa. (3) Testing whether the Learner Worksheet (LKPD) based on the Problem Based Learning (PBL) learning model and cooperative Numbered Head Together (NHT) type is effective for improving the results of Islamic Cultural History at MTs Arifah Gowa. This research is quantitative research with the type of research Quasi Ekperiment. The form of design used is non-equivalent control group design. The population in this study were all students at MTs Arifah Gowa, totaling 883 people. While the sample is class VII 1 and VII.2 each consisting of 28 people, with cluster sampling technique, namely the technique of determining the sample is done randomly. The methods used are observation, test and documentation methods. The research instruments used observation guidelines, learning outcomes tests and documentation guidelines. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive data analysis obtained values, namely the pretest control class with an average value of 68 is in the high category and the posttest with an average value of 77 is in the high category which shows a significant increase in the learning outcomes of students taught using LKPD based on the Problem Based Learning learning model, while in the experimental class the pretest with an average value of 67 is in the high category and the posttest with an average value of 86 is in the very high category which shows a significant increase in the learning outcomes of students taught using LKPD based on the NHT type cooperative learning model. And in the effectiveness test with the N-Gain formula, it is known that the N-Gain value in the control class is 0.149 and the experimental class is 0.295. Because it has a value greater than the significance value of 0.05, it is concluded that both learning models are effective in improving student learning outcomes. The implication in this study is that the use of Problem Based Learning-based Learner Worksheets (LKPD) and NHT-type cooperatives affects student learning outcomes, therefore teachers should disseminate the use of media to be able to improve student learning outcomes. The school is also expected to increase school facilities and infrastructure, especially providing facilities for using LKPD.